Устройство для измельчения изношенных шин - Диденко А. Н. Андрей Николаевич; Самойленко Г. М. Геннадий Михайлович; Юшков Ю. Г. Юрий Георгиевич; Курец В. И. Валерий Исаакович; Таракановский Э. Н. Эдуард Николаевич
опубл. 20.07.95